Implementation of ICT: a comparative study between SMK La Salle Petaling Jaya and SMK Sri Bintang Utara Wilayah Persekutuan / Mohd Shahran Adnan - Adnan, Mohd Shahran (2004)
Trend and style in learning and teaching have been evolving through time. The implementation of Information Communication Technology (ICT) in secondary school will give another new alternative in the educational world. By using ICT in the study and teaching, the teachers and students will have more control over the material that they want to learn and in more manageable ways. In this survey, the focus is on the comparison of factors involved in implementation of ICT between the regular school's teachers and Smart School's teachers within the Klang Valley. This study aims at establishing and identifying the factors that help teachers as well as impede the process of ICT implementation in Malaysian schools. One of the objectives of this study is to look at the perception of teachers, including the school administrators, primarily the principal's role, towards the use of ICT in their schools and classrooms. In this research, there are two populations which are the secondary schools teachers from Sekolah Menengah Kebangsaan La Salle Petaling Jaya (SMLSPJ) and Sekolah Menegah Kebangsaan Sri Bintang Utara in Wilayah Persekutuan (SMSBUWP).The samples as generalized from the populations are 40 respondents from each school and the total sample are 80 respondents from both schools by interviewing them and gave questionnaires. The use of ICT in schools should not be viewed as a pan aced but instead as a tool that is capable of changing the ways in which schools operate. It would be used to remote curriculum and teaching methods. The technology is expensive and complex. It is seldom easy to see how to integrate it into an existing curriculum. Some issues, related to ICT integration in schools that should be considered to ensure success in the implementation process.